Transcriptomic insights into developmental arrest in fluorescent labeling transgenic Asian elephant (Elephas maximus) embryos via inter-order cloning - Pankammoon, Peachanika; Qing, Yubo; Zhao, Heng; Jiao, Deling; Li, Honghui; Wang, Fengchong; Wiriyahdamrong, Thanapa; Guo, Jianxiong; Li, Wengui; Chuammitri, Phongsakorn; Thitaram, Chatchote; Wei, Hongjiang; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAsian elephants (Elephas maximus) provide a unique model for studying cloning in large mammals. As an endangered species with declining populations and limited oocyte availability, interspecies somatic cell nuclear transfer (iSCNT) combined with transcriptomic analysis holds promise for advancing iSCNT embryonic arrest development and further facilitating applications in conservation efforts, therapeutic cloning, and regenerative medicine.MethodsThis study conducted low-input RNA sequencing analyses on transgenic Asian elephant-pig (AE-P) inter-order cloned embryos expressing enhanced green fluorescent protein (EGFP) at the 2- and 4-cell stages. Differential gene expressions, pathway enrichment, and hub gene analyses were performed to identify the molecular mechanisms and core genes influencing normal and arrest development.Results and DiscussionApproximately 25% of clean reads successfully aligned with the Asian elephant genome. The transcriptomic analysis revealed that inter-order cloned embryos with earlier cleavage at the 2- and 4-cell stages exhibited signs of residual transcriptomic memory and incomplete epigenetic reprogramming, while arrested embryos showed indications of nucleocytoplasmic incompatibility and nDNA-mtDNA mismatch. Hub gene analyses indicated core genes such as NDUFC2, NDUFS3, NDUFAB1, SDHC, SDHB, NUP54, NUP43, NUP37, NDC1, CDK1, and CCNB1 linked to energy production, nucleocytoplasmic transport, and cell cycle regulation highlighting the overall challenges in cloning Asian elephant inter-order embryos. Altogether, the analysis of high-throughput sequencing enhances the reliability of iSCNT production in this study, advancing our understanding of cellular reprogramming and molecular roadblocks in AE-P inter-order cloned embryos. Transcriptomic analyses have identified key factors contributing to developmental barriers in iSCNT, offering valuable insights into the complexities of these challenges.